Global challenges in public finance and international relations - Duran, Deniz Sahin, 1979-; Temur, Yusuf, 1967-; Bozdogan, Dogan, 1983- (Business Science Reference, 2018)
"This book examines the present international financial events and institutions, international financial relations, fiscal difficulties and dilemmas, discussions and solutions for potential problems in the postmodern world"--